2019
DOI: 10.1177/0273475319826621
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Written Case Analysis and Reduce Grading Time: The One-Page, Two-Case Method

Abstract: Teaching with cases, especially at universities where cases are not a regular part of the curriculum, poses challenges for both faculty and students. The results in this research present an effective and manageable method to introduce the case analysis process and to facilitate written case analysis for both students and faculty. Experiment 1 compares the effectiveness of a semistructured one-page written case analysis over a traditional case analysis and finds the shorter assignment results in shorter grading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The results are more productive in studies comparing the effectiveness of different forms of case-based learning. Passyn and Billups (2019) found that requiring a one-page case write-up led to better case analyses than a longer writeup (Experiment 1, d = .70) perhaps because the page limit required more editing and therefore greater engagement. Providing clear instructions for case write-ups improved performance (d = .41), but oral practice with a case provided little incremental learning (d = .03).…”
Section: Teacher Choices and Specific Learning Activitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The results are more productive in studies comparing the effectiveness of different forms of case-based learning. Passyn and Billups (2019) found that requiring a one-page case write-up led to better case analyses than a longer writeup (Experiment 1, d = .70) perhaps because the page limit required more editing and therefore greater engagement. Providing clear instructions for case write-ups improved performance (d = .41), but oral practice with a case provided little incremental learning (d = .03).…”
Section: Teacher Choices and Specific Learning Activitiesmentioning
confidence: 94%
“…Passyn and Billups (2019) found that students learned a case writing task better when they participated in an in-class group learning session than when learning alone (Experiment 2, d = .37). Reflecting on these findings, longer group projects that invite specialization of labor and partitioned engagement may undermine learning (Bacon, 2005), while shorter in-class group activities with little specialization of labor and little opportunity for group dysfunction may be beneficial (Passyn & Billups, 2019). However, more research is needed to clarify these mechanisms and effects.…”
Section: Teacher Choices and Specific Learning Activitiesmentioning
confidence: 99%
“…Having students provide written feedback in addition to a quantitative evaluation enhances the learning experience for the assignment submitters as well as the peer graders (Luaces, Díez, & Bahamonde, 2018). Shorter written assignments, particularly involving case analyses also reduce grading time and increase student performance on the assignment (Passyn & Billups, 2019).…”
Section: Peer Assessmentmentioning
confidence: 99%
“…Passyn and Billups (2019) recognise the value of written case analyses on ensuring that each student has prepared the case and decided on a single course of action. In our experience, asking for previous open and closed written questions in the learning management system (LMS), ensures students’ readiness for the discussion.…”
Section: Methodsmentioning
confidence: 99%